Using the Enterprise Architecture Approach to Analyse the Current Performance of Manchester United Football Club - Adlan Azhar, Ahmad Amirul; Badrul Hisham, Badrul Emran; Abu Bakar, Nur Azaliah (Journal of Techno-Social, 2022)
Manchester United Football Club (MUFC) is one of the most successful football clubs in England, if not the world.  However, the football club's recent performance in domestic and European tournaments has left a lot to be desired.  The recent 2021 Europa League final failure encapsulates the football club's decade-long condition.  MUFC's days of competing seriously for trophies in every tournament open to the club are over.  MUFC came close to winning the local league in the 2017 and 2021 seasons but fell short, just like they did in the previous Europa League final in 2021.  Numerous reasons have contributed to the current poor performance streak.  This study aims to apply an enterprise architectural framework to enhance football player performance and manager-player relationships.  This study discovered that MUFC might leverage big data analytics-IT integrated systems by following easy-to-understand enterprise architectural framework phases, which streamlines the adoption process for MUFC